Phosphides or nitrides for better NLO properties? A detailed comparative study of alkali metal doped nano-cages. (August 2017) - Maria,; Iqbal, Javed; Ludwig, Ralf; Ayub, Khurshid
Graphical abstract: Highlights: Alkali metal doped boron and aluminum phosphide nano-cages are evaluated for NLO properties. The NLO response of phosphide nano-cages is compared with nitride nano-cages. Phosphide nano-cages show better NLO properties than the corresponding nitride nano-cages. Conductivity of doped nano-cages is much higher than pristine nano-cages. MAl11 P12 and MB11 P12 show monotonic increase in hyperpolarizability with size of alkali metal. Abstract: Phosphide nano-cages of MX12 P11 and MX11 P12 (where X = B or Al, M = Li, Na, K) are investigated theoretically for geometric, electronic and nonlinear optical (NLO) properties. Alkali metal is doped by replacing (a) aluminum or boron atom and (b) phosphorus atom. Alkali metal doping can remarkably alter the electronic and NLO properties of the nano-cages, regardless of doping site. HOMO-LUMO gap is decreased whereas first hyperpolarizability is enhanced significantly in doped AlP and BP nano-cages. PDOS (partial density of states) analysis suggests that diffuse excess electrons from alkali metal play important role in boosting NLO properties of phosphide nano-cages. TD-DFT calculations are performed to study the effect of alkali metal doping on absorption spectra. Red shift is observed in the UV–vis spectra of all considered nano-cages. Comparison of phosphide nano-cages with nitride nano-cages indicated that doping nitride nano-cages with alkali metal leads to greater hyperpolarizability and NLO response than doping phosphide nano-cages.